A moment for compassion: emerging rhetorics in end-of-life care. Issue 2 (10th February 2018) - Zaman, Shahaduz; Whitelaw, Alexander; Richards, Naomi; Inbadas, Hamilton; Clark, David
Abstract : Compassion is an emotional response to the suffering of others. Once felt, it entails subsequent action to ameliorate their suffering. Recently, 'compassion' has become the flagship concept to be fostered in the delivery of end-of-life care, and a rallying call for social action and public health intervention. In this paper, we examine the emerging rhetorics of compassion as they relate to end-of-life care and offer a critique of the expanding discourse around it. We argue that, even where individuals 'possess' compassion or are 'trained' in it, there are difficulties for compassion to flow freely, particularly within Western society. This relates to specific sociopolitical structural factors that include the sense of privacy and individualism in modern industrialised countries, highly professionalised closed health systems, anxiety about litigation on health and safety grounds, and a context of suspicion and mistrust within the global political scenario. We must then ask ourselves whether compassion can be created intentionally, without paying attention to the structural aspects of society. One consequence of globalisation is that countries in the global South are rapidly trying to embrace the features of modernity adopted by the global North. We argue that unrealistic assumptions have been made about the role of compassion in end-of-life care and these idealist aspirations must be tempered by a more structural assessment of potential. Compassion that is not tied to to realistic action runs the risk of becoming empty rhetoric.